The main strategic documents of the Russian Federation's subjects: analysis, actualization, individualization - P. S. Trifonova (Вестник университета)
The texts of the strategies of socio-economic development of the constituent entities of the Russian Federation are analyzed. The studied database includes 240 strategic documents approved in the period from 1997 to 2020. Based on the analysis of the selected strategic documents, the prerequisites for their actualization are identified. Based on the results of studying the dynamics of the approval of strategic documents, the author’s periodization of the “waves of interest” in the development of socio-economic development strategies is proposed: from the year of the introduction of a new type of planning document to the current stage of development strategies. General ideas about the individualization of strategies for the socio-economic development of territories of different levels are founded.